Levodopa-induced dyskinesia: interplay between the N-methyl-D-aspartic acid receptor and neuroinflammation - Zhang, Fanshi; Liu, Mei; Tuo, Jinmei; Zhang, Li; Zhang, Jun; Yu, Changyin; Xu, Zucai (Frontiers in Immunology, 2023)
Parkinson's disease (PD) is a common neurodegenerative disorder of middle-aged and elderly people, clinically characterized by resting tremor, myotonia, reduced movement, and impaired postural balance. Clinically, patients with PD are often administered levodopa (L-DOPA) to improve their symptoms. However, after years of L-DOPA treatment, most patients experience complications of varying severity, including the "on-off phenomenon", decreased efficacy, and levodopa-induced dyskinesia (LID). The development of LID can seriously affect the quality of life of patients, but its pathogenesis is unclear and effective treatments are lacking. Glutamic acid (Glu)-mediated changes in synaptic plasticity play a major role in LID. The N-methyl-D-aspartic acid receptor (NMDAR), an ionotropic glutamate receptor, is closely associated with synaptic plasticity, and neuroinflammation can modulate NMDAR activation or expression; in addition, neuroinflammation may be involved in the development of LID. However, it is not clear whether NMDA receptors are co-regulated with neuroinflammation during LID formation. Here we review how neuroinflammation mediates the development of LID through the regulation of NMDA receptors, and assess whether common anti-inflammatory drugs and NMDA receptor antagonists may be able to mitigate the development of LID through the regulation of central neuroinflammation, thereby providing a new theoretical basis for finding new therapeutic targets for LID.